2021
DOI: 10.3390/rs13142666
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned While Implementing a Time-Series Approach to Forest Canopy Disturbance Detection in Nepal

Abstract: While deforestation has traditionally been the focus for forest canopy disturbance detection, forest degradation must not be overlooked. Both deforestation and forest degradation influence carbon loss and greenhouse gas emissions and thus must be included in activity data reporting estimates, such as for the Reduced Emissions from Deforestation and Degradation (REDD+) program. Here, we report on efforts to develop forest degradation mapping capacity in Nepal based on a pilot project in the country’s Terai regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…First, to calculate the Land Cover/Land Use and Landscape Integrity indicators, we created two map products. While the methods used to create these map products have significant support in the literature [e.g., 51 , 141 , 142 ], we found that applying them in this specific context had wide margins of error and some unexpected results that provided an opportunity to learn and improve upon these methods. For example, our disturbance maps, which were used for LCLU Indicator 2, showed omission errors in the stable forest class.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…First, to calculate the Land Cover/Land Use and Landscape Integrity indicators, we created two map products. While the methods used to create these map products have significant support in the literature [e.g., 51 , 141 , 142 ], we found that applying them in this specific context had wide margins of error and some unexpected results that provided an opportunity to learn and improve upon these methods. For example, our disturbance maps, which were used for LCLU Indicator 2, showed omission errors in the stable forest class.…”
Section: Discussionmentioning
confidence: 94%
“…Deforestation was defined as a permanent conversion of forested land to non-forested land. Degradation was defined as a process that does not lead to a change in land cover but shows a reduction in tree cover canopy [ 50 , 51 ]. The changes were mapped for the 5-year period 2010–2015, when most of the interventions occurred.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…patches with a closed canopy (Frolking et al 2009). Human disturbances such as selective tree removal, which is common in Nepal, would thus reduce tree cover (Shrestha et al 2013, Aryal et al 2021) and, therefore, forest carbon stock. In contrast, if these sites naturally have sparse tree cover or only a fraction of the patches with tree cover, we would likely expect these sites to be adjacent to other land uses and have a higher probability of disturbance.…”
Section: Fine-scale Gradientsmentioning
confidence: 99%